Long-term decay of serum cholesterol radioactivity: body cholesterol metabolism in normals and in patients with hyperlipoproteinemia and atherosclerosis - Samuel, Paul (1970)
After the intravenous injection of labeled cholesterol, the decay of specific radioactivity of total serum cholesterol was studied in 12 patients for 15-63 wk (average, 45 wk). In some, but not all of the patients studied, the slow slope of the decay curves suggested a deviation from monoexponential behavior, and the data of the slow period of the decay of specific activity were curve fitted by two exponentials. Six patients had serum lipid values regarded as normal and six had hyperlipoproteinemia. The data were analyzed by input-output analysis and yielded the following results. Values for the input rate of cholesterol (I(T)) (the sum of dietary and biosynthesized cholesterol) showed no difference between the normals and patients with hypercholesterolemia. The size of the rapidly miscible pool of cholesterol (M(a)) was significantly higher in the group of hypercholesterolemic patients partly due to increased serum cholesterol levels. The size of the total exchangeable body mass of cholesterol (M) was higher by an average of 49 g in the patients with hypercholesterolemia as compared to normals. The remaining exchangeable mass of cholesterol (M — M(a)) of the hypercholesterolemic subjects was higher by an average of 29 g as compared to normals. These differences were statistically significant.